PENCEGAHAN KEKERASAN BERBASIS GENDER OLEH KONSELOR SPIRITUAL DI LK3 UIN JAKARTA - Nadya Kharima; Ahmad Zaky (Social Welfare Study Program, 2023)
Abstract. This study investigates gender-based violence prevention by spiritual counselors at LK3 UIN Syarif Hidayatullah Jakarta, a state Islamic university. In response to the alarming rates of gender-based violence in universities, the study delves into LK3's efforts to address this issue. Utilizing qualitative methods, including interviews, observations, and literature analysis, the research sheds light on the spiritual counselors' role. Findings highlight a lack of student awareness regarding gender-based violence, including prevalent instances of bullying and derogatory remarks. Spiritual counselors bridge this gap by imparting religious knowledge and supporting vulnerable students. Their proactive strategies involve religious education and emotional assistance, fostering a safer and more respectful university environment. Keywords: Gender-Based Violence, Spiritual Counselors, Prevention Strategies, Higher Education Institutions, Religious Education. Abstrak. Penelitian ini menggali upaya pencegahan Kekerasan Berbasis Gender (KBG) oleh konselor spiritual di Lembaga Konsultasi Kesejahteraan Keluarga (LK3) UIN Syarif Hidayatullah Jakarta, menghadapi angka KBG yang tinggi di perguruan tinggi. Menggunakan metode penelitian kualitatif dengan wawancara, observasi, dan literatur, penelitian ini memberikan gambaran pencegahan KBG dari perspektif spiritual konselor LK3. Temuan menyoroti minimnya pemahaman mahasiswa mengenai KBG, termasuk kasus perundungan dan penghinaan seksis. Konselor spiritual memainkan peran kunci dalam mengisi kesenjangan ini melalui pengetahuan agama dan dukungan emosional. Strategi pencegahan melibatkan edukasi agama dan pendampingan mahasiswa yang rentan terhadap KBG. Penelitian ini menekankan pentingnya bimbingan spiritual dalam menciptakan lingkungan kampus yang lebih aman dan hormat bagi semua mahasiswa. Kata Kunci: Kekerasan, Gender, Spiritual.